The Attitude of Generation Z Towards YouTube Skippable Ads: An Empirical Study on Lokalate Ads - Indriani Sandi Putri Nainggolan (Indonesian Journal of Business Analytics, 2021)
As businesses’ marketing activities have migrated to various social media platforms, competition between advertisers to attain market’s attention is getting more intense. As a result, marketers began to involve manipulative and provocative strategies to steal market’s attention. This, however, lead to a boomerang effect where consumers develop negative attitude towards advertisement—especially among Generation Z as one of the biggest demographic groups. Aimed to fill in the knowledge gap regarding this issue, specifically in Medan, this research investigates how attitude towards advertisement is affected by several antecedents, namely informativeness, entertainment, and irritation. Multiple linear regression analysis is employed to assess the relationship between variables. The result shows that informativeness along with entertainment have positive effect on attitude towards advertisement, whereas irritation has negative effect. This indicates that marketers should consider these factors to create an effective advertisement that can evoke positive attitude among audiences.